In vivo bioimaging tracks conditionally replicative adenoviral replication and provides an early indication of viral antitumor efficacy - Davydova, Julia (Cancer Sci, 2009)
In vivo monitoring of conditionally replicative adenovirus (CRAd) replication and assessing its correlation to CRAd biological effects are necessary for the clinical development of gene therapy. Noninvasive bioimaging is one current approach which can monitor in vivo CRAd replication and functional effect. Here we describe a novel cyclooxygenase‐2 (Cox2) promoter‐controlled CRAd that was modified to contain firefly luciferase in its E3 region; this modification permitted serial bioluminescence imaging of viral replication in vitro and in vivo. In vitro luciferase expression correlated with viral replication and cytolytic effect. In vivo bioluminescence imaging showed dynamic representation of the viral replication level in athymic nude mice bearing subcutaneous tumor xenografts. Importantly, in vivo luciferase bioluminescence measured 6 days after viral administration significantly correlated with CRAd antitumor effect at day 36. Thus, our system could detect viral replication and predict in vivo therapeutic outcome based on early imaging. Further development of this approach may improve patient safety, enhance clinical trial conduct, and provide mechanistic insight into CRAd function in vivo. (Cancer Sci 2009; 00: 000–000)